A Study of the Relationships Among Chinese Multicharacter Words, Subtypes of Readers, and Instructional Methods. (January 2016) - Ho, Fuk-chuen; Siegel, Linda S.
This article reports the results of two studies examining the effectiveness of the whole-word and analytic instructional methods in teaching different subtypes of readers (students with normal reading performance, surface dyslexics, phonological dyslexics, and both dyslexic patterns) and four kinds of Chinese two-character words (two regular [RR], two irregular [II], one regular, one irregular [RI], and one irregular, one regular [IR]). The approaches employed were the analytic method, which focuses on highlighting the phonological components of words, and the whole-word method, which focuses on learning by sight. Two studies were conducted among a sample of 40 primary school students with different reading patterns. The aim was to examine the relationships among different subtypes of readers, two-character words, and instructional methods. In general, students with a surface dyslexic pattern benefited more from the analytic methods. Regarding combinations of different kinds of two-character words, all subtypes of students performed better in reading RR words than in reading II words.